Entrepreneurial ecosystem of the University of València - Comeche Martínez, José Manuel (2018)
This article is part of the process of describing, analyzing, and exploring the Incubation and Technology Transfer Model of the University of València towards the Valencian society, in order to find anchoring points for initiatives, including improvement of services and procedures defined and proposed by the University itself. The University of València, in its 2016-2019 strategic plan, is defined as "a university that promotes basic and applied research, and scientific and technological development", whose aim is "to value the results of the investigation". To this end, it has developed an ecosystem of services and resources that strive to capture, generate and manage talent and the academic knowledge available, to see who the doers are and how they do it, as well if they are able to transfer the research results into products, services, processes, technological innovations, etc., in the different areas of sectoral application. Our work concludes with a constructive comment that emphasizes the need to balance the generated ecosystem leading it to the establishment of the financial factor, and points to the need of finding "new" ways to implement the transfer process, with the purpose of generating an effective flow towards business.